Study on reinforced concrete beam-column joints subjected to different fires and loadings considering CFRP retrofitting - Đoàn Văn Đẹt; Đinh Hoài Luân; Võ Bá Huy; Cao Văn Vui (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ)
This paper investigates the postfire performance of reinforced concrete beam-column joints under monotonic and cyclic loadings with and without Carbon Fiber Reinforced Polymer (CFRP) retrofitting. Experiments were conducted on nine beam-column joints. One of these was not exposed to fire to be used as a control specimen. The other eight specimens were separated into two groups, which were exposed to 45-min and 75-min fires. After exposure to fire, in each group, one pair of joints were retrofitted with CFRP, while the other pair were not retrofitted. Of each pair, one joint was subjected to monotonic loading, while the other joint was subjected to cyclic loading. The results of fire tests indicated that, after fire exposure, the concrete color changed from grey to light pink. Under loading, a plastic hinge appeared at the beam end close to the column surface, and diagonal cracks appeared at the intersection of the beam and columns. The load-carrying capacity of joints was reduced by about 11% due to fire exposure. The ultimate load of CFRP-retrofitted joints was 12.9 - 17.1% higher than that of the control joint.